2015
DOI: 10.1002/pssa.201431871
|View full text |Cite
|
Sign up to set email alerts
|

Generic origin of subgap states in transparent amorphous semiconductor oxides illustrated for the cases of In-Zn-O and In-Sn-O

Abstract: We present a microscopic interpretation for the appearance and behaviour of subgap states in stoichiometric and oxygen-deficient, amorphous In-Zn-O (a-IZO) and In-Sn-O (a-ITO) derived from a density functional theory analysis using a self-interaction-correction scheme. Our findings concerning the defect structures and the resulting deep levels are qualitatively similar to earlier results on a-IGZO and a-ZTO and in agreement with recent experimental results. Based on our extensive set of DFT results for In-, Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…1) [22]. In the case of these amorphous TOSs, structural imperfections led to the formation of an antiparabolic shaped extra state just below the original conduction band bottom, which played an essential role in the transistor switching of TOS-based TFTs [27,28]. In the present case, the almost linear shaped extra DOS (i.e., tail states) formed just below the conduction band bottom, possibly due to an oxygen deficiency.…”
mentioning
confidence: 68%
“…1) [22]. In the case of these amorphous TOSs, structural imperfections led to the formation of an antiparabolic shaped extra state just below the original conduction band bottom, which played an essential role in the transistor switching of TOS-based TFTs [27,28]. In the present case, the almost linear shaped extra DOS (i.e., tail states) formed just below the conduction band bottom, possibly due to an oxygen deficiency.…”
mentioning
confidence: 68%
“…These tail states [73,75,87,91] originate from the charge localization at undercoordinate oxygen atoms (with a coordination number 3 or below; c.f., Figure 1e) and contribute to the optical absorption within the visible range, that is, at 2-3 eV (Figure 3c). The degree of localization and the energy location of the tail states with respect to the valence band edge depends strongly on the oxygen/metal ratio (as discussed in more details later in this section) and on the cation composition (see Section 5.4).…”
Section: Carrier Generation and Defect Formation In Aossmentioning
confidence: 99%
“…The research area of transparent conducting oxides (TCOs) dates back to 1907 when CdO was reported to combine both optical transparency in the visible range and good electrical of amorphous indium oxide appeared in 2009, [61] followed by models of electron transport in multi-cation AOSs, [62][63][64][65][66][67] DFT calculations of defect formation, [68][69][70][71][72][73][74][75] and statistical descriptions of amorphous network. [76][77][78] However, several key questions regarding the nanostructure and morphology, crystallization, carrier generation, and conductivity mechanisms in AOSs remain unanswered and require a unified theoretical framework capable of handling all these aspects in tandem.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the physics behind such a system should be identical. Since metallic agglomerates are in fact the intrinsic n-type dopants of ZTO [40] (which corresponds to oxygen vacancies in the more common language employed by the scientific community) the valence change mechanism maintains its validity. The observed 1D RS can be explained by conventional filament formation from the oxygendeficient region close to the titanium top electrode toward the platinum bottom electrode.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%